PENDIDIKAN ISLAM INKLUSIF SEBAGAI FONDASI PEMBANGUNAN MANUSIA DAN PEMBENTUKAN KARAKTER DI ERA DIGITAL - Akhmadi; Siti Aisyatul Arifah (International Conference on Humanity Education and Society (ICHES), 2026)
The development of digital technology has brought significant changes in various aspects of life, including education. Digitalization opens up opportunities for more inclusive and equitable access to education, yet it also presents challenges such as the weakening of students' character, tendencies toward dehumanization, and increasing social inequality. In this context, Islamic education plays a strategic role as the foundation for human development that emphasizes not only intellectual aspects but also character building and human values. This article aims to conceptually examine the role of inclusive Islamic education in character building and human development in the digital age. The method used is a conceptual study based on literature review, analyzing classical and contemporary sources relevant to Islamic education and human development theory through content analysis and thematic analysis. The study identifies five main dimensions: (1) inclusive Islamic education as a humanistic educational paradigm that acknowledges diversity, (2) character formation through the internalization of values such as honesty, responsibility, empathy, justice, and moderation, (3) significant contribution to human development through the integration of spiritual, moral, and social dimensions, (4) implementation challenges including limited educators' understanding and minimal integration of character values in technology utilization, and (5) a conceptual model of character-based inclusive Islamic education that integrates Islamic values, inclusivity principles, and ethical use of digital technology. The study concludes that inclusive Islamic education can serve as a foundation for character-based, just, and sustainable human development in the digital age through synergy among values, educational systems, and social contexts.